Listening English Song as Habit in Improving Listening Skills: SMP Pius Students’ Perception - Mitha Dwi Rahmadani; Dwi Ario Fajar (FKIP, Universitas Palangka Raya, 2026)
Listening comprehension remains one of the most demanding receptive skills in English Language Teaching (ELT), frequently hindered by student anxiety and constrained exposure within conventional classroom settings. This qualitative descriptive study investigates middle school students' perceptions regarding the autonomous habit of listening to English songs outside the formal curriculum and its perceived contribution to their listening proficiency. Utilizing a purposive sampling approach, qualitative data were gathered from eighth-grade students at SMP Pius Pekalongan through open-ended questionnaires, semi-structured interviews with key informants, direct classroom observations, and documentary analysis, complemented by teacher triangulation. The data were iteratively processed following the Miles and Huberman framework, comprising data reduction, data display, and verified conclusion drawing. The findings demonstrate that students hold highly favorable perceptions toward self-directed song listening, categorizing it as an engaging daily pastime rather than a rigorous academic obligation. This continuous exposure significantly facilitates implicit vocabulary acquisition, attunes learners to native phonetic articulation, and lowers anxiety levels in alignment with Krashen’s Affective Filter Hypothesis. Additionally, students identified tracks characterized by moderate tempos, clear articulation, and accessible lyrical structures as the most efficacious for auditory comprehension. While informal song exposure markedly reinforces student confidence and auditory familiarity, it functions optimally as a supplementary learning strategy alongside structured pedagogical instruction.